2010
DOI: 10.1002/jcp.22273
|View full text |Cite
|
Sign up to set email alerts
|

c‐Jun N‐terminal kinase is largely involved in the regulation of tricellular tight junctions via tricellulin in human pancreatic duct epithelial cells

Abstract: Tricellulin (TRIC) is a tight junction protein at tricellular contacts where three epithelial cells meet, and it is required for the maintenance of the epithelial barrier. To investigate whether TRIC is regulated via a c-Jun N-terminal kinase (JNK) pathway, human pancreatic HPAC cells, highly expressed at tricellular contacts, were exposed to various stimuli such as the JNK activators anisomycin and 12-O-tetradecanoylphorbol 13-acetate (TPA), and the proinflammatory cytokines IL-1β, TNFα, and IL-1α. TRIC expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 45 publications
5
51
0
Order By: Relevance
“…In fishes, another member of the TAMP subfamily, occludin, has also been found in a broad array of tissues (7,10). In addition, broad TRIC expression in trout was comparable to reports in mammals (26,33,35,47,50), where it has been found in testis, small intestine, kidney, lung, liver, brain, inner ear, retina, epidermal cells, and pancreas. Furthermore, cytosolic TJ proteins such as zonula occludens 1 (ZO-1) also show broad and consistent expression patterns in fish tissues (8).…”
Section: Discussionsupporting
confidence: 65%
“…In fishes, another member of the TAMP subfamily, occludin, has also been found in a broad array of tissues (7,10). In addition, broad TRIC expression in trout was comparable to reports in mammals (26,33,35,47,50), where it has been found in testis, small intestine, kidney, lung, liver, brain, inner ear, retina, epidermal cells, and pancreas. Furthermore, cytosolic TJ proteins such as zonula occludens 1 (ZO-1) also show broad and consistent expression patterns in fish tissues (8).…”
Section: Discussionsupporting
confidence: 65%
“…Enteritidis AvrA Inhibits Cellular JNK Activation-ZO-1 is regulated by the JNK signaling pathway (25,39,40). Using Western blotting, we found that JNK signaling was activated, as indicated by the marked increase in JNK phosphorylation, in Caco-2 BBE, HCT116, and SKCO15 cells following S. Enteritidis colonization (Fig.…”
Section: F-h)mentioning
confidence: 83%
“…Gene silencing of tricellulin in epithelial cells has been shown to induce irregularities in cellular shape and disorganisation of F-actin fibers, owing to the inactivation of Cdc42 by tricellulin and accordingly impairment of junctional tension (74). Furthermore, in normal human pancreatic duct epithelial cells, the c-Jun N-terminal kinase (JNK) pathway has been found to regulate tricellulin expression at tricellular junctions in addition to epithelial barrier function (75). Interestingly, occludin silencing has been linked with tricellulin relocalisation to bicellular tight junctions, highlighting an important role for occludin in tricellular tight junction maintenance (71) despite the fact that occludin and tricellulin are not known to physically interact with each other (73).…”
Section: Several Isoforms Of the Gene Encoding Tricellulin Tric Hmentioning
confidence: 99%